Effects of bentonite on rumen fermentation and duodenal flow of dietary components in sheep fed palm kernel cake by-product - Ivan, M; Neill, L; Alimon, R; Jalaludin, S (2001)
Feeding palm kernel cake (PKC) by-product, which contains relatively high levels of copper (Cu), may result in hepatic Cu accumulation in ruminants and in chronic Cu toxicity in sheep. Supplements of bentonite were efficient in alleviating accumulation of Cu in the liver. The objective of the present experiment was to determine the effects of supplementation of bentonite (2% of dietary dry matter) on rumen fermentation, duodenal flow of amino acids (AA), and digestibility in sheep fed PKC-based diets. Rumen and duodenum-cannulated sheep were fed three isonitrogenous PKC-based diets, control (C), C plus bentonite (CB) and CB plus casein (CBC) as experimental treatments. The C and CB diets contained 94.5% PKC, and were assigned four sheep each, while the CBC diet contained 82% PKC and 2.2% casein, and was assigned three sheep. Cellulose was used to bring diets C and CBC to 100% of dry matter. After 12 days on the diets the sheep were placed in metabolism cages and feces, duodenal digesta and rumen fluid were sampled on days 14 and 15, 16 and 17, and 18 and 19, respectively. On the three diets, rumen pH ranged between 5.9 and 6.0, while ammonia nitrogen (mg/100 ml) ranged between 5.2 on the C diet and 8.5 on the CBC diet. The total volatile fatty acid concentration (mmol/l) was 41, 51 and 65 on diets C, CB and CBC, respectively. The duodenal flow (g/kg organic matter intake) of total AA on the C, CB and CBC diet was 130, 141 and 136, respectively. The total tract digestibility (%) ranged between 61.9 and 71.3 for organic matter, 65.0 and 72.2 for neutral detergent fiber, and 73.5 and 76.6 for nitrogen. None of the differences among means of the measured parameters were significant in the present experiment (p > 0.05). It was concluded that supplementation of PKC-based diets with 2% bentonite had no appreciable effect on rumen fermentation, duodenal flow of AA or digestibility in sheep.